A full participation agreement on global emission reduction through strategic investments in R&D - Uwe Kratzsch; Gernot Sieg; Ulrike Stegemann (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2010)
If an emission reduction agreement with participation of all players is not enforceable because politicians are too myopic or not able to commit themselves to sustainable policies or costs of reducing emissions are too high, strategic investments in research and development (R&D) of green technology, for example sustainable drive-trains, can pave the way for a future treaty. Although no player will rationally reduce emissions on its own, investments in R&D by at least one player can change the strategic situation of negotiations to control emissions: Emission abatement costs will decrease so that a treaty with full participation can be achieved in future periods through time consistent sustainable policies.
Keywords: Q54; F53; O30; H41; 330; emissions; discount factor; commitment; endogenous technical change; repeated prisoner's dilemma